Insulin promotes vascular smooth muscle cell proliferation and apoptosis via differential regulation of tumor necrosis factor‐related apoptosis‐inducing ligand - Harith, Hanis Hazeera; Di Bartolo, Belinda A.; Cartland, Sian P.; Genner, Scott; Kavurma, Mary M. (Wiley-Blackwell Publishing, 2016)
Background: Insulin regulates glucose homeostasis but can also promote vascular smooth muscle (VSMC) proliferation, important in atherogenesis. Recently, we showed that tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) stimulates intimal thickening via accelerated growth of VSMCs. The aim of the present study was to determine whether insulin‐induced effects on VSMCs occur via TRAIL. Methods: Expression of TRAIL and TRAIL receptor in response to insulin and glucose was determined by polymerase chain reaction. Transcriptional activity was assessed using wild‐type and site‐specific mutations of the TRAIL promoter. Chromatin immunoprecipitation studies were performed. VSMC proliferation and apoptosis was measured. Results: Insulin and glucose exposure to VSMC for 24 h stimulated TRAIL mRNA expression. This was also evident at the transcriptional level. Both insulin‐ and glucose‐inducible TRAIL transcriptional activity was blocked by dominant‐negative specificity protein‐1 (Sp1) overexpression. There are five functional Sp1‐binding elements (Sp1‐1, Sp1‐2, Sp‐5/6 and Sp1‐7) on the TRAIL promoter. Insulin required the Sp1‐1 and Sp1‐2 sites, but glucose needed all Sp1‐binding sites to induce transcription. Furthermore, insulin (but not glucose) was able to promote VSMC proliferation over time, associated with increased decoy receptor‐2 (DcR2) expression. In contrast, chronic 5‐day exposure of VSMC to 1 µg/mL insulin repressed TRAIL and DcR2 expression, and reduced Sp1 enrichment on the TRAIL promoter. This was associated with increased cell death. Conclusions: The findings of the present study provide a new mechanistic insight into how TRAIL is regulated by insulin. This may have significant implications at different stages of diabetes‐associated cardiovascular disease. Thus, TRAIL may offer a novel therapeutic solution to combat insulin‐induced vascular pathologies.